The impact of patient sex on the response to intramyocardial mesenchymal stem cell administration in patients with non-ischaemic dilated cardiomyopathy. Issue 13 (13th February 2020) - Florea, Victoria; Rieger, Angela C; Natsumeda, Makoto; Tompkins, Bryon A; Banerjee, Monisha N; Schulman, Ivonne H; Premer, Courtney; Khan, Aisha; Valasaki, Krystalenia; Heidecker, Bettina; Mantero, Alejandro; Balkan, Wayne; et al.
Abstract: Aims: Sex differences impact the occurrence, presentation, prognosis, and response to therapy in heart disease. Particularly, the phenotypic presentation of patients with non-ischaemic dilated cardiomyopathy (NIDCM) differs between men and women. However, whether the response to mesenchymal stem cell (MSC) therapy is influenced by sex remains unknown. We hypothesize that males and females with NIDCM respond similarly to MSC therapy. Methods and results: Male ( n = 24) and female ( n = 10) patients from the POSEIDON-DCM trial who received MSCs via transendocardial injections were evaluated over 12 months. Endothelial function was measured at baseline and 3 months post-transendocardial stem cell injection (TESI). At baseline, ejection fraction (EF) was lower ( P = 0.004) and end-diastolic volume (EDV; P = 0.0002) and end-systolic volume (ESV; P = 0.0002) were higher in males vs. females. In contrast, baseline demographic characteristics, Minnesota Living with Heart Failure Questionnaire (MLHFQ), and 6-min walk test (6MWT) were similar between groups. EF improved in males by 6.2 units ( P = 0.04) and in females by 8.6 units ( P = 0.04; males vs. females, P = 0.57). EDV and ESV were unchanged over time. The MLHFQ score, New York Heart Association (NYHA) class, endothelial progenitor cell-colony forming units, and serum tumour necrosis factor alpha improved similarly in both groups. Conclusion: Despite major differences in phenotypic presentation of NIDCM in males and females, this study is the first of its kind to demonstrate that MSC therapy improves a variety of parameters in NIDCM irrespective of patient sex. These findings have important clinical and pathophysiologic implications regarding the impact of sex on responses to cell-based therapy for NIDCM. Graphical Abstract: